2002
DOI: 10.1038/sj.bjp.0704725
|View full text |Cite
|
Sign up to set email alerts
|

Increased arginase activity underlies allergen‐induced deficiency of cNOS‐derived nitric oxide and airway hyperresponsiveness

Abstract: 1 A de®ciency of constitutive nitric oxide synthase (cNOS)-derived nitric oxide (NO), due to reduced availability of L-arginine, importantly contributes to allergen-induced airway hyperresponsiveness (AHR) after the early asthmatic reaction (EAR). Since cNOS and arginase use L-arginine as a common substrate, we hypothesized that increased arginase activity is involved in the allergeninduced NO de®ciency and AHR. 2 Using a guinea-pig model of allergic asthma, we addressed this hypothesis by examining the e ects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
146
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 52 publications
6
146
1
3
Order By: Relevance
“…proline, valine, homoserine and alanine), but reversed the drop in glucose, mannose, galactose, arabinose and galacturonic acid in asthma. The arginine-proline pathway is implicated in asthma (Meurs et al 2002;Lara et al 2008), whereby increase in arginase activity can lead to augmented conversion of L-arginine to urea and ornithine. Ornithine is converted to proline and then to valine (Weeda et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…proline, valine, homoserine and alanine), but reversed the drop in glucose, mannose, galactose, arabinose and galacturonic acid in asthma. The arginine-proline pathway is implicated in asthma (Meurs et al 2002;Lara et al 2008), whereby increase in arginase activity can lead to augmented conversion of L-arginine to urea and ornithine. Ornithine is converted to proline and then to valine (Weeda et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these pathways are implicated in cell proliferation and collagen production. Indeed, increased arginase activity is linked to airway hyper responsiveness or decreased airway smooth muscle relaxation in asthma 26,27 . Moreover, elevated arginase I expression increases airway smooth muscle proliferation by mechanisms involving the production of polyamines 28 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first to have demonstrated the role of increased arginase activity in tobacco associatedpulmonary endothelial dysfunction. Increased arginase activity has also been associated with airway hyperresponsiveness [33,34]; we previously demonstrated that increased arginase activity is involved in airway sensitivity in smokers [35]. Overall, elevated arginase activity may be one of the mechanisms underlying both pulmonary arterial dysfunction and bronchial dysfunction [36].…”
Section: Discussionmentioning
confidence: 91%